Effectiveness of different investigation procedures in detecting anthropogenic impacts on coralligenous assemblages - Piazzi, Luigi; Balata, David; Cecchi, Enrico; Gennaro, Paola; Serena, Fabrizio (Scientia Marina, 2014)
Coralligenous habitat is one of the most important and sensitive habitats of the Mediterranean Sea and several different sampling procedures are currently used in the ecological investigations of coralligenous assemblages. This study aimed to assess the efficacy of different methods in detecting anthropogenic impacts on coralligenous habitat. In particular, the choice of sampling methods, the level of taxonomic resolution, the sampling area, the number of replicates and the spatial scales for detecting possible impacts were evaluated. Results showed that photographic samples larger than 1800 cm2, numbers of replicates larger than 10, the use of taxa and morphological groups as assemblage descriptors, and sampling designs with a high replication at small spatial scales are a valid methodological procedure in impact evaluation studies based on coralligenous assemblages.